2002
DOI: 10.1103/physrevb.65.245110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and control of the metal-to-insulator transition in rocksalt tantalum nitride

Abstract: We identify the previously unknown mechanism whereby rocksalt Ta x N can be continuously tuned from conducting to insulating through changes in stoichiometry. Experimental measurements on thin films, combined with electronic structure calculations on a host of native defects, show that the tunability arises from changes in the free electron concentration as a result of localization at Ta vacancies (V Ta ). The observed enhanced resistivity, transition from electron to hole conduction at xϳ0.6, and diminished m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
57
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 15 publications
10
57
1
Order By: Relevance
“…These results are in good agreement with data from the literature [5,10,21]. Yu et al [22] reported that the generated Ta vacancies under N-rich experiment conditions are responsible for metal-insulator transition in the rock-salt TaN phase. These results are in good agreement with the cell parameter evolution previously described, which was also attributed to the formation of Ta vacancies under N-rich conditions.…”
Section: Electrical Resistivitysupporting
confidence: 93%
“…These results are in good agreement with data from the literature [5,10,21]. Yu et al [22] reported that the generated Ta vacancies under N-rich experiment conditions are responsible for metal-insulator transition in the rock-salt TaN phase. These results are in good agreement with the cell parameter evolution previously described, which was also attributed to the formation of Ta vacancies under N-rich conditions.…”
Section: Electrical Resistivitysupporting
confidence: 93%
“…Tantalum nitride has many different stable phases (solid solution bcc-a-phase, hcp-gphase, and hexagonal e-phase) and metastable phases (bcc b-TaN, hexagonal d-phase TaN, hexagonal WC structure y-TaN, B1 NaCl d-TaN x , hexagonal Ta 5 N 6 , tetragonal Ta 4 N 5 , and orthorhombic Ta 3 N 5 ) [8,9]. Yu et al reported that the resistivity of NaCl d-TaN x changed significantly from highly conductive (10 À1 mO cm) to insulating (10 3 mO cm) through changes in stoichiometry depending on N 2 pressure and temperature during the film deposition [10].…”
Section: Introductionmentioning
confidence: 96%
“…However the relationship between the barrier efficiency and material structure has not been established. On the theoretical side, research has focused on bulk properties 15 and electronic structures of TaN compounds, [16][17][18] the thermal stability of Cu/TaN/Si stacking structures, 19 and statistical modeling of atomic diffusions. 20 However, the crucial issues such as why and how TaN compounds work as diffusion barrier materials are still not well understood.…”
Section: Introductionmentioning
confidence: 99%